STUDY ON THE CHANGES IN CHARACTERISTICS OF HIGHLY EXPANSIVE SOIL IN CIREBON DUE TO ADDITION OF EGGSHELL POWDER - Gerry T Padantha; Billy Tanadi; Hasbullah Nawir (Universitas Udayana, 2025)
Expansive soils, which swell with increased moisture and lose strength compared to their dry state, can cause landslides, structural cracks, and other shrink–swell related issues. Lime treatment is commonly used to mitigate these problems but is unsustainable and leaves a large carbon footprint. As an alternative, eggshell powder (ESP), rich in calcium, is proposed as a stabilizing agent. Soil properties were tested in accordance with ASTM standards. Consistent with Lee and Suedkamp, high-plasticity soil shows no distinct optimum dry density, making it difficult to establish a clear pattern of changes in this property. ESP addition reduces the Atterberg limits and Methylene Blue Value, lowers the swelling potential, and increases the unconfined compressive strength (UCS). The calcium content in ESP decreases the soil’s capacity to swell, although the effect appears limited due to remaining organic components. A significant improvement in UCS was observed with 5% ESP at 14 days of curing, increasing strength from 181.87 kPa to 327.49 kPa, while the most notable reduction in swelling potential occurred with 15% ESP at 7 days of curing. However, both UCS and swelling potential showed no consistent trend, likely due to complex interactions of organic materials in ESP that reduce its effectiveness in soil stabilization.